(untitled) (Medical Forum Monthly, 2021)
Objective: To study the Prevalence of Anemia in pregnant women in the pandemic of COVID-19. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Allama Iqbal Memorial Teaching Hospital Sialkot and Sardar Begum Teaching Hospital Sialkot department of Obstetrics and Gynecology during March 2019 to September 2020. Materials and Methods: Two hundred pregnant women were selected for this study. The history and examination of each woman was conducted and blood was taken for complete blood count (CBC). The informed written consent was taken before examination and sample collection of the pregnant women. The Ethical Committee permission of was considered before collecting the data and get publishing in Medical Journal. The data was analyzed for results by SPSS version 20. Results: The prevalence of Anemia in pregnant women during COVID-19 was maximum 60(30%) in age group 20-25 years and was minimum 18(09%) in age group 41-44 years. The prevalence of Anemia in pregnant women during COVID-19 was maximum in lower class75 (37.50% and minimum 58(29%) in middle class The prevalence of Anemia in pregnant women during COVID-19 was maximum 85(42.50%) of Hemoglobin 6-7gm/dl and was minimum 15(07.50%) of Hemoglobin 12-13gm/dl. Conclusion: It was concluded from the study was that Anemia was prevalent in pregnant women because most of the pregnant women did not come to hospital for Ante natal care. Therefore, iron advised on diet and iron supplement was not received.